Durability of geopolymers with industrial waste. (June 2022) - de Oliveira, Leandro B.; de Azevedo, Afonso R.G.; Marvila, Markssuel T.; Pereira, Elaine C.; Fediuk, Roman; Vieira, Carlos Mauricio F.
Abstract: Industrialization and urban growth have led to a high demand for Portland cement in the world. However, cement production contributes to the increase in the greenhouse effect with gas emissions and energy waste. It is estimated that the cement industry is responsible for 7% of all CO2 generated in the world. In recent years, several alternatives to Portland cement have been researched. Among these alternatives, alkali activated materials, including geopolymers, are considered a viable alternative for obtaining sustainable building materials, formed through the reaction of a source rich in aluminosilicate together with an alkaline activator. This review article addresses some of the main industrial by-products (FGD residue, fly ash, blast furnace slag and glass waste) with potential to be used in the production of geopolymers, the differences between alkali activated materials and geopolymers, the main products obtained in alkaline activation reaction and the factors that interfere with the kinetics of reactions. Subsequently, this article reviews the durability of geopolymeric materials with industrial residues, exposed to carbonation, acid corrosion, sulphate solution, chloride penetration, heat temperature, freezing and thawing, drying and wetting and thermal shock. Finally, some inferences and future analysis about AAM durability were made.